Categorizing processing via the Meat Science Lexicon. (1st October 2017) - Carr, C.C.; Scheffler, J.M.; Johnson, D.D.
Abstract: All meat is processed to varying degrees, even when consumed raw. Meat which has had ingredients added such as salt, phosphate, or seasonings prior to being merchandized to the end user have been subjected to further, rather than minimal processing. Improving safety and shelf-life, honoring history, adding value and convenience, diversifying flavor, and improving sustainability are all contributing reasons why science and art combine in various meat processing applications.